New Synthesis Method of AuNPs Using Moringa oleifera Extract as Bioreductor and Potential Study as Colorimetric Microplastic Detection - Thohir, Muhammad Bakhru; Setyaningrum, Dyah; Saputra, Arya Ananda; Nursaida, Marta Citra (Hasanuddin University, 2025)
Nanoparticles are multipurpose materials that have been utilized in the medical, energy, and environmental monitoring fields. The advantage of nanoparticles is that they have unique physicochemical properties such as surface area, optical activity, and surface modifiability. One of the important uses of nanoparticles is for environmental monitoring. This is because the surface of nanoparticles could be modified, and with their small size, they could reach analytes in difficult matrices. However, the synthesis of nanoparticles has been an unsustainable process. Therefore, the synthesis of AuNPs using bioreductors finds its urgency. The aim of this research is to determine the optimum conditions for the synthesis of AuNPs-MO, the character of the synthesized AuNPs-MO, and to study the application of AuNPs-MO for monitoring microplastic pollutants. This research was conducted through the stages of extraction, determination of optimum conditions, characterization, and literature study of the potential of AuNPs-MO as a detector. Determination of optimum conditions was carried out by applying variations in pH and precursor-reducing agent ratio. Characterization of AuNPs-MO was done with FTIR and PSA. In addition, microplastic detection models with AuNPs-MO have been obtained directly and indirectly. From this series of experiments, satisfactory results have been obtained.